Updating the technique of caesarean section in the Maternity Institute "Alberto Peralta Ramos" - Raimondi, Domingo (2015)
Modern concepts that should govern the conduct of uterine suture is analyzed. It discloses the procedure devised by one of us (Dr. Domingo Raimondi), used since 1956 and since then simplified use since 1961 increasingly simple technique, supported by pathological anatomical and clinical-surgical and experimental studies.